Musculoskeletal Progenitor/Stromal Cell-Derived Mitochondria Modulate Cell Differentiation and Therapeutical Function - Jorgensen, Christian; Khoury, Maroun (Frontiers in Immunology, 2021)
Musculoskeletal stromal cells’ (MSCs’) metabolism impacts cell differentiation as well as immune function. During osteogenic and adipogenic differentiation, BM-MSCs show a preference for glycolysis during proliferation but shift to an oxidative phosphorylation (OxPhos)-dependent metabolism. The MSC immunoregulatory fate is achieved with cell polarization, and the result is sustained production of immunoregulatory molecules (including PGE2, HGF, IL1RA, IL6, IL8, IDO activity) in response to inflammatory stimuli. MSCs adapt their energetic metabolism when acquiring immunomodulatory property and shift to aerobic glycolysis. This can be achieved via hypoxia, pretreatment with small molecule-metabolic mediators such as oligomycin, or AKT/mTOR pathway modulation. The immunoregulatory effect of MSC on macrophages polarization and Th17 switch is related to the glycolytic status of the MSC. Indeed, MSCs pretreated with oligomycin decreased the M1/M2 ratio, inhibited T-CD4 proliferation, and prevented Th17 switch. Mitochondrial activity also impacts MSC metabolism. In the bone marrow, MSCs are present in a quiescent, low proliferation, but they keep their multi-progenitor function. In this stage, they appear to be glycolytic with active mitochondria (MT) status. During MSC expansion, we observed a metabolic shift toward OXPhos, coupled with an increased MT activity. An increased production of ROS and dysfunctional mitochondria is associated with the metabolic shift to glycolysis. In contrast, when MSC underwent chondro or osteoblast differentiation, they showed a decreased glycolysis and inhibition of the pentose phosphate pathway (PPP). In parallel the mitochondrial enzymatic activities increased associated with oxidative phosphorylation enhancement. MSCs respond to damaged or inflamed tissue through the transfer of MT to injured and immune cells, conveying a type of signaling that contributes to the restoration of cell homeostasis and immune function. The delivery of MT into injured cells increased ATP levels which in turn maintained cellular bioenergetics and recovered cell functions. MSC-derived MT may be transferred via tunneling nanotubes to undifferentiated cardiomyocytes and leading to their maturation. In this review, we will decipher the pathways and the mechanisms responsible for mitochondria transfer and activity. The eventual reversal of the metabolic and pro-inflammatory profile induced by the MT transfer will open new avenues for the control of inflammatory diseases.